ANALISIS PENGARUH PROMOSI INSTAGRAM DAN KUALITAS PRODUK TERHADAP MINAT BELI PELANGGAN ROCCOS - Intan Nusanti; Febe Yuanita Ratna Indudewi (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2022)
The purpose of this research is to find out whether Instagram promotion and product quality affect buying interest of Roccos customers. Roccos, is a business in culinary field owned by four students of Universitas Ciputra that has been operated since March 21, 2018 in which recently launchin new product in 2021, that is, potato snack with four different taste variants. Data source in this research uses primary data that is obtained through questionnaire result that has been distributed using google form to prospective respondents who have ever known Roccos product through Instagram or at least heard or tried new Roccos product, have bought new Roccos product or at least have consumed new Roccos product, and Roccos Instagram followers or at least have ever visited to Roccos Instagram account. By using measurement scale of Likert 1 to 5 in which the largest rate will indicate that the respondents strongly agree (SS), 4 Agree (S), 3 Quiet Agree (CS), 2 Disagree (TS), and 1 Strongly Disagree (STS). From this questionnaire distribution, the reseacher successfully obtains as many as 57 respondents. This research is done with quantitative research approach method by using multiple linear regression analysis technique with the help of SPSS statistical program. The following is the finding result of this research : Y=0.892+ 0.165X₁+0.314X₂+e. The result states that each variable has been tested is valid and reliable. The research also proves that there is positive and significant effect between instagram promotion (X1) and product quality (X2) on buying interest (Y) of Roccos customers.